Regulation of virulence gene expression in Streptococcus pyogenes: Determinants of differential mRNA decay - Bugrysheva, Julia V (Landes Bioscience, 2010)
Differential mRNA stability is an important mechanism for regulation of virulence factors in Streptococcus pyogenes (group A streptococcus, GAS), a serious and prevalent human pathogen. We have described 2 Classes of mRNA in GAS that are distinguishable by (1) stability in the stationary phase of growth, (2) kinetics of decay in exponential phase and (3) effect of depletion of RNases J1 and J2 and polynucleotide phosphorylase (PNPase) on decay in exponential phase. We discuss features of the structure of an mRNA that appear to be important for determining the Class to which it belongs and present a model to explain differential mRNA decay.